CONCEPT OF CULTURAL AND EDUCATIONAL SPACE IN MODERN PEDAGOGICAL SCIENCE - Олеся Смолінська (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The paper considers the content of the concept of cultural and educational space from pedagogical theory positions. A classification of the studies of cultural and educational space has been made in this research. Author's criteria for grouping definitions of cultural and educational space and other notions used in a synonymic sense have been outlined. The following definitions of this subject by scientists have been presented: as a physical factor of spatial organization, organizational and managerial category, factor of pedagogical influence, the coordinate system for society ethnic values, space of social and psychological communications, the object of philosophical and educational discourse, factors of the appearance of a person's subjectness, the circumstance of metaphor formation of speech assimilation of reality.